Efektivitas Media Video Animasi dalam Pembelajaran Seni Tari untuk Meningkatkan Kreativitas Motorik Anak Usia Dini - Rofiqoh Rofiqoh; Hifatul Inayah; Diana Pramudita; Lailatul Usriyah (Jurnal Ilmiah Cahaya Paud, 2026)
This study aimed to determine the effectiveness of using animated video media in dance learning to improve the motor creativity of early childhood children. Using a pretest-posttest control group design, this study employed a quantitative approach with a quasi-experimental methodology. The study sample consisted of one control group and one experimental group, each comprising 36 children aged 5 to 6 years. Methods such as documentation and observation were used to collect the data. The study’s findings indicate that children’s motor creativity is significantly influenced by the use of animated video media. The mean score of the experimental group increased from 58.4 to 86.7, while the mean score of the control group increased from 57.9 to 71.2. The findings of the effectiveness test for the experimental group were statistically significant at the 0.001 level. Through more engaging and participatory learning activities, animated video media helps children develop their motor skills, imagination, and self-confidence. Consequently, children’s motor creativity can be nurtured through the use of animated video media in dance education.